Menjembatani Penelitian Kualitatif dan Kuantitatif Irfan Sanusi - Irfan Sanusi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2009)
The quantitative method of research inspired by August Comte in his Philosophy of Positivism, is contradictory with the qualitative method of research which is one of the methods elaborated and derived from rationalism. I suggest that quantitative research models– descriptive model, correlation, experiment and quasi-experiment – should be placed on the grand theory as well as the the social context, or to follow the logic of qualitative method, so that research invention is inseparable from the grand situation. In light of this view, I suggest that the two contradictory methods of research be combined.